A Novice English Teacher’s Efforts to Enhance Students’ Reading Comprehension on Narrative Text Through SQ4R Method, What Can We Learn? - Annisa Yusti Desiyanti; Miftahul Rachmat; Tri Ilma Septiana; Pitriah Pitriah (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The main objective of the present study is to observe the efforts of a novice English teacher in applying the SQ4R method to enhance students’ reading comprehension on narrative text at the secondary school level in a rural area of Kota Serang. To achieve this objective, the Kemmis & McTaagart model of classroom action research was chosen as a research design. In addition, this study also involved research collaborators so that the novice English teacher gained valuable inputs in the preparation of lesson plans and objectivity in assessing the quality of learning process. Besides, classroom observation and reading test were used as research instruments. This study was declared successful in cycle 2, when the result of reading test showed that 85.71% of students had achieved the minimum completeness criteria with a mean score of 71.54. In summary, the direct implication of the SQ4R method for students include the development of cognitive skills, enhancement in reading comprehension and retention, as well as generating self-confidence and critical thinking skills.